Ketenggangan Genotipe Jagung (Zea mays L.) Terhadap Cekaman Aluminium - , Syafruddin; Didy Sopandie; , Trikoesoemaningtyas (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2006)
Aluminum (Al) toxicity is the main yield-limiting factor for maize growing on acid soils of tropical regions. This experiment was conducted to screen maize (Zea mays L) genotypes under Al stress in culture solution. The experiment was arranged in a split plot design with three replications. The main plots were Al concentrations (0, 2.5, 5 10, 20, and 40 ppm Al), and the sub plots were 22 maize genotypes. The results indicated that the genotype AMATL-(HS).C2, SATP-(S2)-C6-S0, MRSS-1(S1).C1-29-1, and MRSS-1(S1).C1-57-1  were more tolerant to Al-toxicity than the other genotypes including Antasena. The growth of Al-tolerant genotypes under low concentration of Al (2.5 ppm Al) was stimulated. The Concentration of 5 - 10 ppm Al in nutrient solution was adequate to separate genotypes between tolerant and sensitive genotypes in screening maize genotypes under Al stress. Relative net root length and relative root length were the best variable to be used as Al-tolerance indicators.   Key words: Maize, Al-tolerance,   Al-toxicity